Burden of kidney cancer in China from 1990 to 2021 and predictions for 2036: an age-period-cohort analysis of global burden of disease study 2021 - Yi-Fan Zhang; Yun-Hua Ji; Hao-Zhong Hou; Xiao-Zheng Fan; Bo Yang; Zhen Yao; Hao Wang; Bo Zhang; Long-Long Zhang; Xiao-Jian Yang (BMC Public Health)
Abstract Objective This study aimed to describe the temporal trends and risk factors of kidney cancer (KC) burden from 1990 to 2021, evaluate its age, period, and cohort effects, and project the disease burden over the next 15 years. Methods Data were derived from the 2021 Global Burden of Disease (GBD) study. A joinpoint regression model was used to estimate the average annual percentage change (AAPC) in KC prevalence and mortality, while age-period-cohort analysis was applied to estimate age, period, and cohort effects. We extended the Bayesian age-period-cohort (BAPC) model to predict the disease burden of KC from 2022 to 2036. Results In 2021, the number of incident KC cases in China reached 65,799 (4.62 cases per 100,000 total population). Additionally, KC resulted in 24,867 deaths (1.75 deaths per 100,000 total population).The incidence rate of KC continued to rise from 1.38 per 100,000 in 1990 to 4.62 per 100,000 in 2021, with males consistently exceeding females in case numbers. Meanwhile, KC mortality rose from 0.77 per 100,000 in 1990 to 1.75 per 100,000 in 2021.Throughout the study period, the average annual percent changes (AAPC) in incidence and mortality were 3.92% and 2.61%, respectively. Males exhibited higher prevalence and mortality of KC. In the Age-Period-Cohort (APC) analysis, the risk of KC was observed to increase with advancing age in the age dimension. Period effects analysis revealed an overall downward trajectory in all age groups. Cohort-level analysis indicated that early birth cohorts had higher susceptibility, with those born before 1920–1925 exhibiting a higher risk profile that subsequently decreased over time. Smoking and high body mass index (BMI) were the primary risk factors for KC-related disability-adjusted life years (DALYs) and mortality, while the contribution of occupational exposure to trichloroethylene was relatively minor. By 2036, the age-standardized incidence and mortality of KC are projected to rise to 4.58 and 1.31 per 100,000, respectively. Conclusion To alleviate the disease burden of KC, comprehensive strategies are required, including risk factor prevention in primary care settings, KC screening for the elderly and high-risk populations, and access to high-quality medical services.